Influence of dietary Spirulina inclusion and lysozyme supplementation on the longissimus lumborum muscle proteome of newly weaned piglets - Ribeiro, David M. (2021)
Arthrospira platensis (Spirulina) is a microalga with a high content of crude protein. Its recalcitrant cell wall limits the accessibility of the animal endogenous enzymes to its intracellular nutrients. Enzymatic supplementation aiming to degrade cell walls could benefit microalgae digestibility. The objective of this study was to evaluate the impact of dietary Spirulina and lysozyme supplementation over the muscle proteome of piglets during the post-weaning stage. Thirty piglets were randomly distributed among three diets: control (no microalga), SP (10% Spirulina) and SP+L (10% Spirulina + 0.01% lysozyme). After 4 weeks, they were sacrificed and samples of the longissimus lumborum muscle were taken. The muscle proteome was analysed using a Tandem Mass Tag (TMT)-based quantitative approach. A total of 832 proteins were identified. Three comparisons were computed: SP vs Ctrl, SP+L vs Ctrl and SP+L vs SP. They had ten, four and twelve differentially abundant proteins. Glycogen metabolism and nutrient reserves utilization are seemingly increased in the SP piglets. Structural muscle protein synthesis increased, causing higher energy requirements in SP+L piglets. Our results demonstrate the usefulness of proteomics to disclose the effect of dietary microalgae, whilst unveiling putative mechanisms derived from lysozyme supplementation. Data are available via ProteomeXchange with identifier PXD024083